Towards a Legal Framework for Deploying Carbon Technologies to Address the Environmental Impacts of Gas flaring in Nigeria - Bello, Fatima (Journal of Sustainable Development Law and Policy, 2025)
In 2019, Nigeria contributed 7, 825 million cubic meters (mln m3/yr) to global greenhouse gas emissions. A legal framework has been developed to curb gas flaring and create the incentive to utilise flare gas, which is derived in part from existing legislation, and from market-based incentives. This developed a mechanism to convert waste gas into wealth while protecting health and the environment – a winning formula. Given that the objective of the framework is to guard against waste and protect the environment, it has wasted an opportunity to convert flare emissions into wealth by creating a framework for the deployment of carbon technologies to guard against the environmental impact of gas flaring. This is pertinent because as the industry transits to low carbon, and as oil exploration is expected to continue in the immediate future, critical stakeholders are now investing in carbon technologies. The legal framework mostly channels its technologydriven approach towards utilising flare gas. However, this article finds that the mechanism for converting flare gas to wealth in the legal framework presents an opportunity to harness the potential carbon technologies to develop mechanisms for capturing and utilising carbon from flare facilities, building other industry ecosystems, and developing other environmentally sustainable value chains. As Nigeria continues to explore its petroleum resources, a framework to encourage its deployment is missing. This article analysis carbon technologies highlighting how they are deployed to tackle emissions and utilise emitted carbon. It also reviews the legal framework for curbing gas flaring in Nigeria and proposes by way of recommendation a legal framework for the deployment of carbon technologies to curb the environmental impact of gas flaring in Nigeria that paves the way for incentivising and developing other environmentally sustainable industrial ecosystems that utilise captured emissions from flare sites.